2015
DOI: 10.1186/s40645-014-0031-4
|View full text |Cite
|
Sign up to set email alerts
|

The geospace response to variable inputs from the lower atmosphere: a review of the progress made by Task Group 4 of CAWSES-II

Abstract: The advent of new satellite missions, ground-based instrumentation networks, and the development of whole atmosphere models over the past decade resulted in a paradigm shift in understanding the variability of geospace, that is, the region of the atmosphere between the stratosphere and several thousand kilometers above ground where atmosphere-ionosphere-magnetosphere interactions occur. It has now been realized that conditions in geospace are linked strongly to terrestrial weather and climate below, contradict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
71
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(71 citation statements)
references
References 148 publications
(167 reference statements)
0
71
0
Order By: Relevance
“…Consequently, short‐term (a few days) tidal variability cannot be resolved. We thus employ daily tidal diagnostics from “tidal deconvolution.” The method (Oberheide et al, 2002) has been validated and proven its usefulness for studying the short‐term variability of various diurnal tides using WINDII and SABER data (e.g., Lieberman et al, 2013, 2015; Oberheide et al, 2015; Pedatella et al, 2016).…”
Section: Datamentioning
confidence: 99%
“…Consequently, short‐term (a few days) tidal variability cannot be resolved. We thus employ daily tidal diagnostics from “tidal deconvolution.” The method (Oberheide et al, 2002) has been validated and proven its usefulness for studying the short‐term variability of various diurnal tides using WINDII and SABER data (e.g., Lieberman et al, 2013, 2015; Oberheide et al, 2015; Pedatella et al, 2016).…”
Section: Datamentioning
confidence: 99%
“…In such cases, GW amplitude growth with increasing altitude can be dramatic, yielding amplitudes and momentum fluxes (per unit density) that can be several or many decades larger than near the GW source [e.g., Vadas , ; Fritts and Vadas , ; Fritts and Lund , , hereafter FL11]. These various dynamics have global implications extending into the thermosphere [e.g., Oberheide et al , ; Yiğit and Medvedev , ], but their parameterizations in global models remain simplistic at present [ Kim et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…From this global analysis, they found that the influence of the diurnal eastward-propagating mode with wavenumber-3, DE3, is particularly strong in determining the longitudinal structure of its amplitude, e.g., during equinoxes and June solstice. This feature was also observed for other parameters in the low-latitude upper atmosphere (see for a review, e.g., Oberheide et al 2015) demonstrating the close relationship between atmospheric tides and ionospheric electrodynamics. Values for EEJ and the eastward electric field are now regularly derived from Swarm observations for each dayside orbit .…”
Section: Introductionmentioning
confidence: 63%